Modification of alternate wetting and drying (AWD), a proven irrigation strategy for rice production, to reduce the production of mosquitoes that transmit malaria - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
For 2019, this is listed as stage 1 because we are testing how a modified version of a proven management strategy can have a positive impact on human health. The URL provides a brief description of the study.